2020
DOI: 10.3892/ol.2020.12392
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor intron 1 polymorphism and microsatellite instability in sporadic colorectal cancer

Abstract: Epidermal growth factor receptor (EGFR) expression is commonly upregulated in sporadic colorectal cancer (CRC) and its high expression is associated with poor prognosis in patients with CRC. CA-SSR1 is a dinucleotide CA repeat of the EGFR gene that can modulate EGFR transcription and is a potential target of the mismatch repair machinery in tumours with microsatellite instability (MSI). In the present study, 160 sporadic colon cancer samples were analysed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…The rs763317 G>A polymorphism is located in intron 1, 6.9 kilobases downstream of the polymorphism region of the dinucleotide CA repeat (near the second enhancer) in the EGFR gene [35]. Analyses of the Mitogen-Activated Protein Kinase/Extracellular-signal-Regulated Kinase (MAPK/ ERK) signaling system [36] demonstrated that the MAPK/ ERK pathway was the center of frequently altered genes throughout the progression of multiple primary lung cancers, including mutated downstream genes and altered upstream activators.…”
Section: Discussionmentioning
confidence: 99%
“…The rs763317 G>A polymorphism is located in intron 1, 6.9 kilobases downstream of the polymorphism region of the dinucleotide CA repeat (near the second enhancer) in the EGFR gene [35]. Analyses of the Mitogen-Activated Protein Kinase/Extracellular-signal-Regulated Kinase (MAPK/ ERK) signaling system [36] demonstrated that the MAPK/ ERK pathway was the center of frequently altered genes throughout the progression of multiple primary lung cancers, including mutated downstream genes and altered upstream activators.…”
Section: Discussionmentioning
confidence: 99%
“…Se considera que un alelo es corto cuando las repeticiones CA son menores o iguales a 16 y un alelo es largo cuando son mayores a 17 repeticiones CA. La longitud de los alelos de este polimorfismo se correlacionan inversamente con la actividad transcripcional del gen EGFR (45,46,47). Graciano et al, 2008 (48) evaluaron el polimorfismo CA-SSR-1 conjuntamente con el SNP 61 A>G del EGF en una cohorte de 110 pacientes con CCRm cuyo estado de la mutación de KRAS era desconocido, tratados con irinotecán más cetuximab y encontraron que los pacientes con dos alelos con menos de 17 repeticiones y un genotipo 61GG presentaron una mayor SLP y SG, en cambio, Loupakis et al, 2014 (49) estudiaron 115 pacientes con CCRm y no hallaron diferencias significativas tanto en la SLP (p= 0,991) como en la SG (p = 0,261) en los portadores de alelos cortos o largos.…”
Section: Polimorfismos: Kras-lcs6 Y Ccdn1unclassified